Women Economic Empowerment during Covid-19 Crisis and Transition in BRICS Countries - Tinuade Adekunbi Ojo (Journal of BRICS Studies)
The paper reviews the BRICS policies in rebuilding economies equity and fairness. All economies are affected by the global pandemic, which has damaged most economies and led to a worldwide public health emergency. The paper adopts a qualitative approach by exploring secondary sources to analyse the role of the BRICS community on women's economic empowerment during the Covid-19 pandemic. It presents a descriptive narrative in the context of the study. The findings project that the BRICS community still lacks strategic policy implementation that integrates women into the BRICS economy. As a result, there is a massive gap in women's economic representativeness and the need to promote access and affordable policies and education-related initiatives that enhance gender inclusion. It recommends that BRICS communities ensure closer cooperation with various stakeholders, national organisations, private businesses, and multinationals to promote gender equality in their respective economies.